2016
DOI: 10.1002/cyto.a.22904
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles for the detection of cell surface antigens in mass cytometry

Abstract: Mass cytometry has pioneered >40-parameter single-cell analyses that allow for the characterization of complex cellular networks at unprecedented depth. Up to 135 parameters can be simultaneously detected, but limited availability of metal tags suitable for labeling of specific probes prevents optimal exploitation of the analytical capacity of mass cytometers. To this end, we here establish the application of elemental silver nanoparticles (AgNP) of different size for reporting cell surface antigens on human l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 39 publications
1
37
0
1
Order By: Relevance
“…This approach enables the simultaneous analysis of over 30 cellular features, for example,the presence of particular receptors,for millions of cells at ar ate of around 2000 cells s À1 . [109][110][111] Here,w e present some of the recent single-cell applications of this technique. [108] Mass cytometry represents at ransition between targeted and untargeted methods,w here fewer than 10 and more than 100 analytes, respectively,a re identified.…”
Section: Immunomarkers Offer High Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…This approach enables the simultaneous analysis of over 30 cellular features, for example,the presence of particular receptors,for millions of cells at ar ate of around 2000 cells s À1 . [109][110][111] Here,w e present some of the recent single-cell applications of this technique. [108] Mass cytometry represents at ransition between targeted and untargeted methods,w here fewer than 10 and more than 100 analytes, respectively,a re identified.…”
Section: Immunomarkers Offer High Selectivitymentioning
confidence: 99%
“…Recent advances in mass cytometry have been discussed in detail elsewhere. [109][110][111] Here,w e present some of the recent single-cell applications of this technique.…”
Section: Immunomarkers Offer High Selectivitymentioning
confidence: 99%
“…To date this promising technique is mainly used for human cells as an effective tool for drug development or improvement of therapeutic programs ranging from infectious disease to cancer (Bendall et al, 2011; Gavasso et al, 2016; Robinson and Mao, 2016; Baca et al, 2017; Baumgart et al, 2017). Also other inorganic nanoparticles have been lables (Vancaeyzeele et al, 2007; Lin et al, 2014; Tong et al, 2016; Schulz et al, 2017) but were in the focus of biodistribution experiments (Yang et al, 2017). Limited studies have been reported on microbial cells (Leipold et al, 2011; Miyashita et al, 2014), where, e.g., a combination of a metal-based membrane stain and lectins, conjugated to lanthanide-chelating polymers, was used to differentiate Escherichia coli cells based on their cell surface polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…One of the research fields that may greatly benefit from these capabilities is development of the advanced nanoagents for targeted drug delivery . Indeed, investigation of the particle–cell interactions with IFC can yield statistical information about the agent specificity , kinetics of its internalization and subsequent localization within the cells , expression levels of cells surface receptors , and their affinity. Furthermore, it can quantitatively assess the cytotoxicity of the agent and its payload .…”
mentioning
confidence: 99%